Effects of corporate governance disclosure on profitability of public listed firms in Tanzania - Magwana Ngollo; Beny Mwenda (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2022)
This study investigated the effect of corporate governance information (CGI) disclosure on firms' profitability in the Dar es Salaam Stock Exchange (DSE). Twenty-one listed companies were studied for a period ranging from 2006 to 2021 using a mixed research method with an explanatory sequential design. Return on equity (ROE) and Return on Assets (ROA) was employed as dependent variables in the panel data analysis. CGI disclosure was an independent variable. The control variables were geographical diversification, firm age, size, and sales growth. Secondary data was obtained from DSE. Qualitative data was gathered via semi-structured interviews. Thematic analysis and a random effect model with two estimates (1 and 2) were used to analyze qualitative and quantitative data. The findings suggested a positive and significant effect of CGI disclosure on firm profitability. The findings add to the body of knowledge by signifying stakeholder theory. The study concluded that Disclosure of CGI might undeniably result in increased profitability. We recommended that firm managers look closely at CGI disclosure, enhance their disclosure practices, and invest in disclosure strategies that benefit stakeholders.